2018
DOI: 10.3762/bjnano.9.177
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Ge mole fraction in improving the performance of a nanoscale junctionless tunneling FET: concept and scaling capability

Abstract: In this paper, a new nanoscale double-gate junctionless tunneling field-effect transistor (DG-JL TFET) based on a Si1− xGex/Si/Ge heterojunction (HJ) structure is proposed to achieve an improved electrical performance. The effect of introducing the Si1− xGex material at the source side on improving the subthreshold behavior of the DG-JL TFET and on suppressing ambipolar conduction is investigated. Moreover, the impact of the Ge mole fraction in the proposed Si1− xGex source region on the electrical figures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The increase in the BTBT generation rate at a higher Ge mf is also evident in figure 7(b). A high Ge mf further changes the threshold voltage to influence the SS value [34]. The Fermi energy level of electrons for varying mf in the ON state was also investigated and is presented in figure 7(c), where it is seen that the Fermi level increases for a corresponding increase in mf.…”
Section: Impact Of Variation In Mole Fractionmentioning
confidence: 99%
“…The increase in the BTBT generation rate at a higher Ge mf is also evident in figure 7(b). A high Ge mf further changes the threshold voltage to influence the SS value [34]. The Fermi energy level of electrons for varying mf in the ON state was also investigated and is presented in figure 7(c), where it is seen that the Fermi level increases for a corresponding increase in mf.…”
Section: Impact Of Variation In Mole Fractionmentioning
confidence: 99%
“…Both the gates are connected to common supply voltage for smooth and equal control over the channel. Furthermore, the metallic gate with work function ϕ m = 4.8 eV is optimized for the OFF-state current along with ON-state current which results in high I ON /I OFF ratio with V gs = 1.0 V, V ds = 1.0 V. [10][11][12][13][14][15] The inner gate oxide and outer gate oxide are also of 1 nm in thickness and HfO 2 is used to further improve the electrical characteristics of device. For the same, a uniform doping profile has been used N d = 1 Â 10 19 cm À3 in all regions like which is irrespective of hetero-interfaces.…”
Section: Device Structure and Design Parametersmentioning
confidence: 99%
“…The device has shown better performance characteristics, with improved linearity and distortion metrics making it suitable for low-power applications. Ferhati et al [17] reported a dual gate junctionless TFET that employs SiGe/germanium for the source/drain material and silicon for the channel material. This innovative design yields a remarkable subthreshold swing of 42mV/decade and an exceptional I ON /I OFF ratio of 115dB.…”
Section: Introductionmentioning
confidence: 99%